Role Conflict Related Job Stress among Construction Project Professionals: The Moderating Role of Age and Organization Tenure (Construction Economics and Building, 2021)
Demographic variables play a vital role in determining stress occurring from workplace demands. Role conflict is a major workplace demand, specifically in the context of construction. However, the way demographic variables influence the stress occurring from role conflict is less explored in the literature. Specifically, the literature does not fully explain the positioning of age and organization tenure on the relationship between role conflict and job stress. Hence, the present study evaluates the moderating role of age and organization tenure on the relationship between role conflict and job stress. A survey was conducted by distributing the questionnaire directly to randomly selected project-level employees of ten large private contractors in Sri Lanka. A total of 274 valid respondents were collected and used to run a factor analysis validated hierarchical regression analysis to assess the research hypotheses. The results showed that role conflict has a positive direct effect on job stress. The findings further revealed that the impact of role conflict on job stress is high for young employees in the construction industry, as young employees do not possess the necessary life skills or experience to cope with role conflict. Contrary to the authors’ expectations, there is no significant contribution from organization tenure to the relationship of role conflict and job stress. Since the young employees are more vulnerable to role conflict, special considerations should be given to improve the well-being of the young workforce. Hence, it is recommended that contractors should assign seasoned supervisors who can nurture the young employees and act as mentors. The supervisors should give clear instructions and inform what the young subordinates need to do when confronted with non-overlapping requests or orders from the other parties involved in the project. Besides, organizations must conduct periodic conflict management and resolution training programs to help the employees cope with the conflicts that occur in the workplace, which is the path to lessen the impact of role conflict as organization tenure accumulates.